Integrated utilization of algal biomass and corn stover for biofuel production. (15th March 2016) - Yue, Zhengbo; Ma, Ding; Peng, Shuchuan; Zhao, Xiang; Chen, Tianhu; Wang, Jin
Highlights: Algal hydrolysate can be used as reaction medium to enhance ethanol production. Soluble protein and Ca 2+ were the active components for the enzymatic process. Algal residue was potential nitrogen source for methane production from corn stover. Algal biomass could be integrated into the ethanol process of corn stover. Abstract: This paper describes a novel route for the utilization of algal and lignocellulosic biomass for biofuel production. Dilute sulfuric acid treatment was employed to destroy the rigid algal cells and generate algal hydrolysate. Algal hydrolysate was used as the reaction medium for the enzymatic hydrolysis of lignocellulose from corn stover. The acid treatment parameters were optimized based on the enzymatic efficiency of corn stover digestion and the promotion mechanism is discussed. The algal residues from the acid treatment process were co-digested with corn stover to generate methane. This study showed that algal hydrolysate can be used as a supplemental feedstock and reaction medium to enhance ethanol production. Furthermore, the residues could be utilized as the nitrogen source during the anaerobic digestion of corn stover.